Implementasi Metode Contextual Teaching and Learning (CTL) Pada Pembelajaran Bahasa Arab di Madrasah Tsanawiyah - Thontowi; Sutipyo Ru'iya (STAI Terpadu Yogyakarta, 2023)
Arabic is a language that has unique difficulties in learning it. Therefore, learning Arabic requires the right strategy so that students can achieve the predetermined competencies. This article describes the implementation of Contextual Teaching and Learning (CTL) learning strategies in learning Arabic at Madrasah Tsanawiyah. This research is a naturalistic qualitative research with a descriptive approach. Primary data was obtained from an Arabic teacher and secondary data was obtained from five students. Collecting data using in-depth interviews and observation techniques. Data analysis through three stages, namely data reduction, data presentation, and drawing conclusions. This research resulted that learning Arabic in MTs with the CTL strategy went through three main stages, namely planning by taking into account the competencies to be achieved, the condition of students' abilities, and students' learning styles. The implementation of classroom learning applies the Contextual Teaching and Learning strategy by connecting material with students' experiences in the real world, using several learning media available in madrasas. The last stage of the learning process is to evaluate learning by implementing an authentic evaluation system that pays attention to all aspects and domains and includes process assessment in the final grade decision.